Pengembangan Lembar Kerja Siswa Berbasis Team Game Tournament Dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran Matematika Kelas V - Alifia Mutia Rafifah; Anis Afifah (Institut Agama Islam Negeri Ponorogo, 2024)
The development of Team Game Tournament-based student worksheets in theMathematics subject on fraction calculation operations was developed becauseinnovation was needed in creating a fun learning concept. Therefore, thisresearch aims to produce TGT-based student worksheets, to find out theeffectiveness of using TGT-based student worksheets on learning outcomes.This type of research is Research and Development (R&D) with the ADDIEstages applied to the VB MIN 7 Magetan class. The research results forproduct feasibility from validation by two validators are presented indescriptive analysis with the feasible category. In the instrument, users aredeclared eligible to obtain an average percentage of 82%. Meanwhile, theeffectiveness of TGT-based Student Worksheets on learning outcomes wascalculated using the N-Gain Score, getting an average of 0.74 with a highclassification, while the average of the N-Gain Percent was 73.86 with a fairlyeffective classification.